EFEITO DE INSETICIDAS SOBRE A JOANINHA CYCLONEDA SANGUINEA L. (COLEOPTERA, COCCINELLIDAE) E SOBRE O PULGÃO APHIS GOSSYPII GLOVER (HEMIPTERA, APHIDIDAE) EM ALGODOEIRO - Scarpellini, J.r.; Andrade, D.j. De [UNESP] (Instituto Biológico, 2020)
The ladybugs are recognized as important natural enemies of pests such as aphids and scale insects, showing excellent dispersibility in the field and may be favored with environments for refuge and by pesticide selectivity. The goal of this trial was to study the toxicity of insecticides on the predatory coccinellid Cycloneda sanguinea and on its prey, the aphid Aphis gossypii, in the cotton crop. The treatments (expressed in commercial product per hectare) were: flonicamid 500 WG at 50, 80 and 150 g, thiamethoxam 250 WG at 200 g, acetamiprid 200 PS at 150 g, imidacloprid 200 SC at 250 mL, and a control treatment without application. The evaluation of physiological selectivity was made in the laboratory and in the field, observing the effect of insecticides applied directly and indirectly on C. sanguine. The number of surviving aphids and lady beetles was evaluated before and after the application. Based on the results obtained in the laboratory and field, it was concluded that flonicamid presented the highest selectivity to C. sanguinea among the insecticides tested. All treatments were effective for aphid control and there were no significant differences among them.

As joaninhas são reconhecidas como importantes inimigos naturais de pragas, como pulgões e cochonilhas, apresentando excelente capacidade de dispersão no campo e podem ser favorecidas com ambientes para refúgio e seletividade dos defensivos agrícolas. O objetivo deste trabalho foi avaliar o efeito de inseticidas sobre a joaninha Cycloneda sanguinea e sobre sua presa, o pulgão Aphis gossypii, na cultura do algodão. Foram estudados os seguintes tratamentos (expressos em quantidade de produto comercial por hectare – p.c./ha): flonicamida 500 WG a 50, 80 e 150 g, thiamethoxam 250 WG a 200 g, acetamiprido 200 PS a 150 g, imidacloprido 200 SC a 250 mL e testemunha sem aplicação. A avaliação da seletividade fisiológica a C. sanguinea foi observada em laboratório e campo, avaliando-se o efeito dos inseticidas aplicados diretamente e indiretamente sobre C. sanguinea. Avaliou-se o número de joaninhas e pulgões sobreviventes após a aplicação. Com base nos resultados pode-se concluir que o inseticida flonicamida apresentou maior seletividade a C. sanguinea em relação aos demais inseticidas. Verificou-se que todos os tratamentos foram eficientes no controle do pulgão e não diferiram estatisticamente entre si.
THE EFFECT OF INSECTICIDES ON THE LADY BEETLE CYCLONEDA SANGUINEA L. (COLEOPTERA, COCCINELLIDAE) AND ON THE APHIDAPHIS GOSSYPII GLOVER (HEMIPTERA, APHIDIDAE) ON COTTON PLANTS
Keywords: Gossypium hirsutum; selectivity; biological control, and natural enemy; Gossypium hirsutum; seletividade; controle biológico e inimigo natura